2016
DOI: 10.1093/jee/tow006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Tolerances of the Spotted-Wing DrosophilaDrosophila suzukii(Diptera: Drosophilidae)

Abstract: The spotted-wing drosophila (Drosophila suzukii Matsumura) is an invasive species of Asian origin that is now widely distributed in North America and Europe. Because of the female's serrated ovipositor, eggs are laid in preharvest fruit, causing large economic losses in cultivated berries and stone fruit. Modeling D. suzukii population dynamics and potential distribution will require information on its thermal tolerance. Large summer populations have been found in regions with severe winter conditions, though … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
97
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 31 publications
18
97
2
Order By: Relevance
“…Jakobs, Gariepy & Sinclair, 2015; Stephens et al, 2015; Plantamp et al, 2016; Ryan et al, 2016). These data corroborate that SWD is a chill susceptible species that does not tolerate brief exposures to sub-zero temperatures (Kimura, 2004; Dalton et al, 2011; Jakobs, Gariepy & Sinclair, 2015; Ryan et al, 2016; Plantamp et al, 2016). At 0 °C, it required about one day to reach 50% mortality in adults and much less time was needed (approximatively 5 h) in pupae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jakobs, Gariepy & Sinclair, 2015; Stephens et al, 2015; Plantamp et al, 2016; Ryan et al, 2016). These data corroborate that SWD is a chill susceptible species that does not tolerate brief exposures to sub-zero temperatures (Kimura, 2004; Dalton et al, 2011; Jakobs, Gariepy & Sinclair, 2015; Ryan et al, 2016; Plantamp et al, 2016). At 0 °C, it required about one day to reach 50% mortality in adults and much less time was needed (approximatively 5 h) in pupae.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, this species is freeze-intolerant and chill-susceptible (Kimura, 2004; Dalton et al, 2011; Jakobs, Gariepy & Sinclair, 2015; Ryan et al, 2016; Plantamp et al, 2016) but has a large thermal tolerance plasticity which likely favors its overwintering (Jakobs, Gariepy & Sinclair, 2015). Another hypothesis for explaining its overwintering success in cold regions is that adults may take refuge into human-made structures or migrate to suitable microclimates during cold periods (Kanzawa, 1939; Kimura, 2004; Cini, Ioratti & Anforta, 2012; Rota-Stabelli, Blaxter & Anfora, 2013; Zerulla et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that common fruit flies with longer preoviposition duration survive longer under cold than flies with short-retention phenotypes (Boulétreau-Merle and Fouillet, 2002). In contrast, no effect of mating status on the overwintering survival has been found in the social wasp Vespula maculifrons (Hymenoptera: Vespidae) (Kovacs and Goodisman, 2012) and in the invasive fruit fly Drosophila suzukii (Diptera: Drosophilidae) (Ryan et al, 2016). …”
Section: Sourcesmentioning
confidence: 99%
“…In contrast, mated flies are more resistant to starvation than unmated ones (Goenaga et al, 2012). The effect of mating status on cold tolerance is up to now largely unknown (but see Boulétreau-Merle and Fouillet, 2002;Ryan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%